Internal Combustion Engines at the Turn of Millennia - Merkisz, Jerzy; Hlavna, Vladimir (Communications - Scientific Letters of the University of Zilina, 1999)
Trends in the development of piston internal combustion engines in a view of tightened ecological regulations (exhaust and noise emissions, fuel consumption) have been presented in this paper. Possibilities and ways of engine design adjustments, both gasoline and diesel type (light and heavy duty), that were undertaken to fulfil the present as well as the expected standards of exhaust toxicity have been discussed as well.